Empowering SDG 16: Electronics-Based Criminal Law Policy to Combat Sexual Violence in Indonesia - Maskun, Maskun; Azisa, Nur; Munandar, M. Aris; Mirzana, Hijrah Adhyanti; Ab Rahman, Nurul Hidayat; Normiati, Normiati; Iskandar, Ismail; Mutawalli, Muhammad (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: Increasing cases of sexual violence, particularly against women, heighten concerns, prompting this group to be vigilant in self-protection. The lack of clarity on electronic-based sexual violence in the TPKS Law may lead to varied interpretations among law enforcement agencies. A normative study is crucial to discern the legislative intent and rationale, ensuring inclusion of these provisions in the TPKS Law. An ideal electronic-based criminal law policy is needed to universally safeguard victims, aligning with the principles of human dignity outlined in SDG 16 of the Global Agenda 2030.Purpose/Objective Study: This investigation sought to delineate the contours of Indonesia's legislative framework pertaining to electronic-based sexual violence within the ambit of criminal law policy. The significance of this inquiry lies in its inherent alignment with and contribution to the realization of Sustainable Development Goal 16, which fundamentally advocates for the promotion of peace, justice, and the fortification of robust institutional frameworks.Design/Methodology/Approach: The research method used is normative legal research with a statutory approach and qualitative analysis.Findings: Law Number 12 of 2022 addresses electronic-based sexual violence in Article 14(1) (a) and (b) but presents drawbacks, particularly concerning consensual consent. Recommending amendments to these articles is crucial to avoid discord with other regulations, striving for an optimal criminal law policy in Indonesia. Legal reforms should consider societal issues and contribute to effective law enforcement. Electronic-based sexual violence legislation must align with both expectations and realities, acknowledging the severity of the offense as a violation of human rights and a significant criminal act under SDG 16. The Indonesian government must establish and enforce laws to combat this activity, crucial for achieving SDG 16. Proposed amendments include introducing supplementary penalties, like revoking access rights to electronic media, to deter offenders.Paper Type: Research Article